2016
DOI: 10.4103/0976-237x.177101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of palatal form on movement of teeth during processing of complete denture prosthesis: An in-vitro study

Abstract: Aim:The aim of this in-vitro study was to assess the influence of shallow and deep palatal forms on the movement of teeth during the processing of complete denture prosthesis.Materials and Methods:Maxillary casts with shallow and deep palatal forms were selected and duplicated to make 10 casts of each palatal form. Base plates were constructed and teeth were arranged in their anatomic positions. Metal pins with true apex were placed on the central groove of the right and left first molars and one on the incisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
0
14
0
2
Order By: Relevance
“…In addition, in the study conducted by Babu et al (2016), concluded that in all fabricated prosthetic bases, the posterior palatal sealing area was the least dimensionally stable region and that denture bases fabricated using the long curing cycle would produce the most stable PMMA denture bases. However, in our study, the opposite happened: the lucitone resin that has the longest curing cycle showed greater dimensional change.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the study conducted by Babu et al (2016), concluded that in all fabricated prosthetic bases, the posterior palatal sealing area was the least dimensionally stable region and that denture bases fabricated using the long curing cycle would produce the most stable PMMA denture bases. However, in our study, the opposite happened: the lucitone resin that has the longest curing cycle showed greater dimensional change.…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados obtenidos muestran diferencia entre los materiales probados, evidenciando que la silicona a 1 000 kg de fuerza mostró mayor estabilidad, asociada a una mayor estabilidad a la contracción 16 de la silicona empleada como revestimiento, independientemente de la técnica de polimerización empleada 23 . Con respecto al yeso su mayor capacidad de retención de humedad puede explicar los mayores valores de distorsión 24 , sobre todo cuando fue aplicado a una fuerza de 1 000 kg de fuerza, sustentando la necesidad de control sobre la fuerza en el prensado protésico como método para disminuir fallas en la prótesis 20,[29][30][31][32][33][34][35] y reducir los cambios dimensionales propios del procesamiento del acrílico 36 .…”
Section: Discussionunclassified
“…Las prótesis completas constituyen una estructura artificial con base acrílica y dientes artificiales, alternativa para recuperar las funciones masticatoria, fonética y estética facial 1,2 perdidas 3,4,6 exigiendo considerar en su construcción variaciones anatómicas [31][32][33] e inclusive psicológicas del paciente 28,29 . La colocación de los dientes artificiales constituye un paso fundamental 30 cuyas modificaciones se encuentran asociadas al desplazamiento de sus bases protésicas 6 , composición del acrílico y de procesamiento 12,18,25 que se traducen en alteraciones oclusales 28 evidenciadas en aumento de la dimensión vertical 34 .…”
Section: Discussionunclassified
“…Six years later, an in vitro study was conducted to assess the influence of different palatal forms (shallow and the deep) on the displacement of the denture teeth during the processing of complete dentures [ 10 ]. To this end, 10 maxillary casts were fabricated by means of duplication for each palatal form.…”
Section: Introductionmentioning
confidence: 99%
“…The distances between the apices of the metallic pins and the fitted reference points were measured in buccopalatal axes at 3 stages (wax-up, deflasking and after finishing). During all processing stages, and for both palatal forms, the results showed statistically significant movements of teeth [ 10 ].…”
Section: Introductionmentioning
confidence: 99%